A Semi-Hierarchical Confirmatory Factor Model for Speeded Data. Issue 5 (2nd September 2020) - Schweizer, Karl; Gold, Andreas; Krampen, Dorothea
ABSTRACT: This paper presents the semi-hierarchical model for confirmatory factor analysis of speeded data. The semi-hierarchical model is achieved by integrating information from the second level of the hierarchical structure of speeded data into the customary confirmatory factor model. The second level of speeded data originates from subsets of participants responding on the basis of different sources. In the semi-hierarchical model, the contributions of the latent variables are modified to reflect characteristics of these subsets. Furthermore, the results of a simulation study comparing the semi-hierarchical model adapted to speeded data and the customary confirmatory factor model are reported. Whereas all the models yielded good model fit according to RMSEA and SRMR, differences between the models were signified by CFI and TLI. The semi-hierarchical model led to the better model fit in data showing noticeable speededness.